Smart Material Test: Optimalisasi Pengujian Bahan Bangunan Berbasis Web - Virma Septiani; Viktor Suryan; Nining Idyaningsih; Direstu Amalia; Asep Muhamad Soleh; Nabilah Hasna Arinda (Universitas Batanghari Jambi, 2023)
In designing material requirements, it is very important to do so that the use of materials becomes effective and efficient. Building materials are an important component in producing a reliable quality building structure. One of the efforts made to ensure the quality of building materials is to carry out material tests in the laboratory. The Palembang Aviation Polytechnic materials laboratory performs the testing procedure manually using a calculator or Microsoft Excel. Manual test calculations pose potential problems (error calculation) and must be well-documented. A materials testing calculation application is made for data processing to get better results and more efficient and effective calculations. The research aims to optimize the data processing of building materials testing using an application so that it is more efficient and effective and the data can be well documented. The material was used to calculate fine aggregate and coarse aggregate tests. The research has implemented a web-based Smart Material Test application using the programming language PHP Version 7, Laravel 8 Framework, and MySQL Database to optimize material testing that is more accurate and well-documented. The results show of testing the application, as many as 50 trials for each test found no application errors, and the average calculation difference was 0.0005 or 0.01744%. Thus, the application is very useful in assisting the calculation of building material testing.